1988
DOI: 10.1902/jop.1988.59.9.595
|View full text |Cite
|
Sign up to set email alerts
|

Dental Status of Adults with and without Periodontitis

Abstract: All 30- to 59-year old subjects (N = 757) from a representative sample of adult Finns (total sample = 1,105), showing advanced periodontitis (marginal bone loss more than 30%, n = 125), were compared with their age- and sex-matched pairs showing no marginal bone loss (n = 291) with respect to the number of intact teeth (no caries experience) present. Both male (n = 83) and female (n = 42) subjects with advanced periodontitis had more intact teeth and intact molars than their matched pairs (113 men and 178 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 12 publications
2
29
0
1
Order By: Relevance
“…Prior to their study, Ashley (24) and Shaw (25) established an inverse relationship between caries and mineral content of plaque and saliva (23,24). Sewon et al also found that periodontitis-affected subjects have more intact teeth than subjects who are free of the disease (26). Therefore, while further investigation remains necessary in the field of smokers' saliva mineral content, our results provide a possible mechanistic explanation of existence of more intact teeth in subjects with periodontitis.…”
Section: Sukob Interesasupporting
confidence: 55%
See 1 more Smart Citation
“…Prior to their study, Ashley (24) and Shaw (25) established an inverse relationship between caries and mineral content of plaque and saliva (23,24). Sewon et al also found that periodontitis-affected subjects have more intact teeth than subjects who are free of the disease (26). Therefore, while further investigation remains necessary in the field of smokers' saliva mineral content, our results provide a possible mechanistic explanation of existence of more intact teeth in subjects with periodontitis.…”
Section: Sukob Interesasupporting
confidence: 55%
“…Prije njih su Ashley (24) i Shaw (25) uspostavili suprotni odnos između karijesa i mineralnog sadržaja plaka i sline (23,24). Sewon i suradnici također su otkrili da kod pacijenata s parodontitisom postoji više intaktnih zuba negoli kod ispitanika koji nemaju parodontitis (26). Dakle, iako su nužna daljnja istraživanja u području mineralnog sadržaja sline pušača, naši rezultati mogu dati mehanističko objašnjenje za postojanje više intaktnih zuba kod osoba s parodontitisom.…”
Section: Bašić I Surunclassified
“…[16] Since 1990, Sewσn et al . with their series of studies,[45671718] have shown that oral mineralization potential of saliva plays an important role in periodontal health and disease. Mineralization favoring factors are known to maintain the integrity of enamel surfaces and intraoral mineralization capacity has been a matter of scientific interest for decades.…”
Section: Discussionmentioning
confidence: 99%
“…that subjects with periodontitis have more intact teeth and more intact molars than subjects who are free of the disease. [6]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation